Emerging Therapeutic Strategies to Restore Regulatory T Cell Control of Islet Autoimmunity in Type 1 Diabetes - Volfson-Sedletsky, Victoria; Jones, Albert; Hernandez-Escalante, Jaileene; Dooms, Hans (Frontiers in Immunology, 2021)
Despite many decades of investigation uncovering the autoimmune mechanisms underlying Type 1 Diabetes (T1D), translating these findings into effective therapeutics has proven extremely challenging. T1D is caused by autoreactive T cells that become inappropriately activated and kill the β cells in the pancreas, resulting in insulin insufficiency and hyperglycemia. A large body of evidence supports the idea that the unchecked activation and expansion of autoreactive T cells in T1D is due to defects in immunosuppressive regulatory T cells (Tregs) that are critical for maintaining peripheral tolerance to islet autoantigens. Hence, repairing these Treg deficiencies is a much sought-after strategy to treat the disease. To accomplish this goal in the most precise, effective and safest way possible, restored Treg functions will need to be targeted towards suppressing the autoantigen-specific immune responses only and/or be localized in the pancreas. Here we review the most recent developments in designing Treg therapies that go beyond broad activation or expansion of non-specific polyclonal Treg populations. We focus on two cutting-edge strategies namely ex vivo generation of optimized Tregs for re-introduction in T1D patients vs direct in situ stimulation and restoration of endogenous Treg function.